Characterisation of the mobility on isoelectric focusing of individual proteins in CSF and serum by immunofixation. Issue 4 (April 1979) - Laurenzi, M A; Link, H
Abstract : The mobility of 17 different proteins in CSF and serum on isoelectric focusing was investigated by subsequent immunofixation using monospecific antisera. Individual proteins yielded identical, often complex band patterns in normal CSF and serum, except transferrin which gave one to two additional bands between pH 5.8-6.4, and the low molecular wieght beta-trace protein and gamma-trace protein, which gave three bands at pH 7.4, 8.0, and 8.4, and a single band at pH 9.5, respectively, on investigation of CSF but not serum. Polyclonal IgC migrated as multiple bands between pH 4.7-8.6. Oligoclonal IgG in CSF in multiple sclerosis and neurosyphilis migrated between pH 8.6-9.5 and was easily discriminated from other proteins.